2006
DOI: 10.1515/ijdhd.2006.5.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality for medical diagnosis, training and education

Abstract: In this paper we present a number of the immersive VR applications that we have developed during the past 18 months as a means of practically demonstrating the modelling approaches previously reported. The paper discusses the usefulness of the different approaches in assisting medical practitioners to diagnose and track conditions which might lead to impairment or disability, and how they can be used to train medical students to recognise such conditions or to undertake associated medical procedures. Initial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Polygonal models are "composed of a set of polygons, with accuracy and smoothness of the models governed by the number of polygons", [22]. Polygon modelling production methodology provides the developer with complete control over the construction of the geometry.…”
Section: Methodsmentioning
confidence: 99%
“…Polygonal models are "composed of a set of polygons, with accuracy and smoothness of the models governed by the number of polygons", [22]. Polygon modelling production methodology provides the developer with complete control over the construction of the geometry.…”
Section: Methodsmentioning
confidence: 99%
“…In medicine, depth clues are very important in surgery; therefore, many studies and clinical trials on the utilization of 3D displays have been investigated [1,2]. In addition, as the main element of VR, 3D technology has been applied to surgical training by medical students [3][4][5]. In recent years, a new surgical method using the 3D technology called heads-up surgery has been proposed and clinically used [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, surveys show that medical practitioners found these types of different approaches to be useful in diagnosing and tracking conditions which might lead to impairment or disability [3]. The study also highlights how AR can be used to train medical students to recognize such conditions or to undertake associated medical procedures [3].…”
Section: Related Workmentioning
confidence: 92%
“…Studies show that there are a lot of gaps in AR research and have also identified what capacity the research needs assistance in [2] and some do not find any immediate advantage of an AR-enhanced training over traditional ways, nevertheless stating that AR-enhanced training gave better results in the long run [12]. In a previous study, surveys show that medical practitioners found these types of different approaches to be useful in diagnosing and tracking conditions which might lead to impairment or disability [3]. The study also highlights how AR can be used to train medical students to recognize such conditions or to undertake associated medical procedures [3].…”
Section: Related Workmentioning
confidence: 99%